Photovoltaic operation in the lower atmosphere and at the surface of Venus. (2nd December 2019) - Grandidier, Jonathan; Kirk, Alexander P.; Jahelka, Phillip; Stevens, Margaret A.; Gogna, Pawan K.; Crisp, David; Osowski, Mark L.; Vandervelde, Thomas E.; Atwater, Harry A.; Cutts, James A.
Abstract: Low‐intensity high‐temperature (LIHT) solar cells are needed for extended photovoltaic power generation in both the lower atmosphere as well as at the surface of Venus. Double‐junction GaInP/GaAs solar cells that may be able to operate and survive, with suitable encapsulation, for several weeks on the 465°C Venus surface have been developed. These solar cells have been optimized for operation under the Venus solar spectrum, which is different from that of the Earth. Abstract : J. Grandidier et al. present low‐intensity high‐temperature (LIHT) solar cells which are needed for extended photovoltaic power generation in both the lower atmosphere as well as at the surface of Venus. Double‐junction GaInP/GaAs solar cells that may be able to operate and survive, with suitable encapsulation, for several weeks on the 465°C Venus surface have been developed. These solar cells have been optimized for operation under the Venus solar spectrum, which is different from that of the Earth.